2020
DOI: 10.2967/jnumed.119.237347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translation of a68Ga-Labeled Integrin αvβ6–Targeting Cyclic Radiotracer for PET Imaging of Pancreatic Cancer

Abstract: The overexpression of integrin αvβ6 in pancreatic cancer makes it a promising target for noninvasive positron emission tomography (PET) imaging. However, currently, most integrin αvβ6-targeting radiotracers are based on linear peptides, which are quickly degraded in the serum by proteinases. Herein, we aimed to develop and assess a 68 Galabeled integrin αvβ6-targeting cyclic peptide (68 Ga-cycratide) for PET imaging of pancreatic cancer. Methods: 68 Ga-cycratide was prepared, and its PET imaging profile was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
3
30
0
1
Order By: Relevance
“…However, due to reduced stability and specificity for the receptor, in vivo results were ambiguous. In a recent study, a cyclic radiotracer specific for integrin αvβ6 ( 68 Ga-cycratide) was used in a pancreatic mouse model for PET imaging ( 32 ). The DOTA-integrin αvβ6 knottin applied here has recently been used in a first-in-human clinical study and has demonstrated a high potential for PDAC targeting ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to reduced stability and specificity for the receptor, in vivo results were ambiguous. In a recent study, a cyclic radiotracer specific for integrin αvβ6 ( 68 Ga-cycratide) was used in a pancreatic mouse model for PET imaging ( 32 ). The DOTA-integrin αvβ6 knottin applied here has recently been used in a first-in-human clinical study and has demonstrated a high potential for PDAC targeting ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…integrin α v β 6, tissue factor, neurotensin receptor 1) or neo-vascularendothelial cells (e.g. integrin α v β 3 ), but few researches focus on the CAFs or PSCs 8 , 14 - 16 . However, given that cancer cells constitute a minority but with a high heterogeneity in pancreatic cancer, targeting CAFs or the activated PSCs has its unique advantages and has become one of the research hotspots 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of new molecular probes, which can target pancreatic cancer specifically and overcome the limitations of 18 F-FDG to some extent, are urgently needed and have great clinical significance. For example, integrin α v β 6 is specifically overexpressed in pancreatic cancer, and its targeting peptide has been radiolabeled with 99m Tc or 68 Ga for the SPECT or PET imaging of pancreatic cancer respectively 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to reduced stability and specificity for the receptor, in vivo results were ambiguous. In a recent study, a cyclic radiotracer specific for integrin αvβ6 ( 68 Ga-cycratide) was used in a pancreatic mouse model for PET imaging ( 32 ). The integrin αvβ6 knottin applied here has recently been used in a first-in-human clinical study and has demonstrated a high potential for PDAC targeting ( 24 ).…”
Section: Discussionmentioning
confidence: 99%